(untitled) (Kronika Bydgoska, 2012)
The Agricultural Office in Bydgoszcz (Kulturamt Bromberg) was established on December 1, 1939. The head office was located in a magniflcent tenement house in 95 Gdańska Street. The objective of the office was to strengthen the German assets in the countryside. Such offices existed in Germany starting from 1919, and their objective was to order the agrarian relations in the countryside, especially to integrate farms. The office’s jurisdiction included statistical analyses, fmancing integrations, division into agricultural districts, water-land melioration matters, forestry, environmental protection, etc. After the outbreak of World War Two, in the areas annexed to the Reich, Kulturamts had to implement the settlement policy of the Third Reich formal-legal and geodesic preparation of agricultural areas for German settlement. The territorial operation of the Kulturamt in Bydgoszcz covered the poviats of Bydgoszcz, Chojnice, Sępólno, Świecie, Tuchola, and Wyrzysk. The Kulturamt in Bydgoszcz employed also Polish people. In the years 1939-1945, there were about 80 Poles. At the end of the year 1944, Poles were sent to Otłoczyn near Aleksandrów Kujawski to build anti-aircraft ditches. There, they lived to see the end of the war.